Analysis of Trends in Anthropometric Characteristics of Montenegrin Recruits from Bar in Period from 1979 to 1987 - Ivan Vasiljevic; Srdja Martinovic; Jovan Gardasevic; Marija Bubanja; Pavle Malovic; Erol Vrevic; Srdjan Redzepagic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2020)
The aim of this study is to observe the trend of anthropometric characteristics in Montenegrin recruits born from 1957 to 1969 from Bar. The sample of respondents in this study numbered a total of 3,670 future soldiers with an average age of 18.19±0.69, who were tested for military service in the period from 20 February 1979 to 21 April 1987. The average body height of the total sample of future soldiers was 175.82±7.04, the average body weight was 68.33±9.73, and the average value of body mass index was 22.06±2.58. The highest body height (178.06±8.67) was in the group of recruits born in 1960. The highest body weight (75.14±5.87) and body mass index (23.96±1.84) was in the group of recruits born in 1957. The value of the body mass index of all future soldiers shows that everyone was in the zone of normal weight. It should be noted that some of these respondents were measured before the age of 18. This means that their growth was not complete. There is a possibility that they on average had a higher body height with the completion of growth and development than this research shows. The results show that all generations of young men from Bar were at that time of a normal weight. This fact is not surprising because it is known that life was different then than it is now. The results of this study are very important in monitoring the trend of these 3 variables in the Montenegrin population, but they also have some limitations. As mentioned above, the rule for recruiting future soldiers was to be tested before the age of 18, when growth and development were not complete yet, and the results after the completion of the growth and development of the respondents would probably be slightly different from these results. Also, some generations had a small number of recruits